An investigative analysis of the security weaknesses in the evolution of RFID enabled passport. (1st January 2012) - Bogari, Eyad Abdullah; Zavarsky, Pavol; Lindskog, Dale; Ruhl, Ron
Since the introduction of radio frequency identification (RFID) enabled passports, the system has been plagued with various vulnerability issues that prove to compromise the e-passport security. To date, three generations of e-passports have been introduced by the International Civil Aviation Organization (ICAO) and the European Union (EU). The first two generations of e-passports are being issued worldwide. This paper presents the evolution of these passports over the years to develop taxonomy of the weaknesses and to serve as a reference point detailing security vulnerabilities linked to the RFID e-passport features in the three generations. The findings can also assist in profiling possible attack vectors on the existing RFID enabled passports and in developing comprehensive RFID e-passport risk mitigation strategies. To illustrate the importance of a comprehensive risk strategy when using RFID e-passport, the attack process modelling method is used to highlight the possible attacks and weaknesses which could result from not using one or more security features.